Rituximab in primary Sjögren's syndrome: a ten-year journey. (November 2014) - Carubbi, F; Alunno, A; Cipriani, P; Bartoloni, E; Ciccia, F; Triolo, G; Gerli, R; Giacomelli, R
Primary Sjögren's syndrome (pSS) is an autoimmune disorder affecting exocrine glands and characterized in most cases by a rather mild clinical picture. However, a subgroup of pSS patients experience systemic extraglandular involvement leading to a worsening of disease prognosis. Current therapeutic options for the treatment of pSS are mainly empirical, often translated by other autoimmune diseases, and recent systematic reviews have highlighted the lack of evidence-based recommendations for most of the drugs commonly employed in the spectrum of extraglandular involvement. Because of the well-established role of B-lymphocytes in the pathogenesis of pSS, a B-cell targeting therapy may represent a new and intriguing therapeutic approach; in this context, growing evidence suggests that B-cell depletion by rituximab (RTX) is also effective in pSS. Of interest, besides clinical efficacy, RTX also showed biologic effects, consistently affecting the inflammation and the lymphoid organization that occur in target tissue. Moreover, the good results observed in the published trials after RTX treatment in pSS should represent the starting point to develop evidence-based guidelines for the use of biologic therapy in this disease.